Caudal Regression and Encephalocele: Rare Manifestations of Expanded Goldenhar Complex - Gabriella D'Angelo; Lucia Marseglia; Salvatore Aversa; Sara Manti; Caterina Cuppari; Mariaconcetta Cutrupi; Carmelo Salpietro; Eloisa Gitto (Hindawi Limited, 2017)
Oculoauriculovertebral spectrum, or Goldenhar Syndrome, is a condition characterized by variable degrees of uni- or bilateral involvement of craniofacial structures, ocular anomalies, and vertebral defects. Its expressivity is variable; therefore, the term "expanded Goldenhar complex" has been coined. The Goldenhar Syndrome usually involves anomalies in craniofacial structures, but it is known that nervous system anomalies, including encephalocele or caudal regression, may, rarely, occur in this condition. We report two rare cases of infants affected by Goldenhar Syndrome, associated with neural tube defects, specifically caudal regression syndrome and nasal encephaloceles, to underline the extremely complex and heterogeneous clinical features of this oculoauriculovertebral spectrum. These additional particular cases could increase the number of new variable spectrums to be included in the "expanded Goldenhar complex."